School-Based Management in Creating Healthy Schools in Elementary Schools - Sumiyati Sumiyati; Rahmat Mulyono (Universitas Wiralodra, 2023)
Ngunut Playen Gunungkidul State Elementary School is located near the Cemoro Jajar tourist attraction and is known for being beautiful, clean, and comfortable. Likewise, the surrounding environment, including Ngunut State Elementary School. This research aims to obtain a fact-based picture in the form of data and information regarding school-based management in creating healthy schools. The purposes of this research include: (1) To find out about school-based management at SDN Ngunut. (2) To find out the efforts of a healthy school at SDN Ngunut. (3) To determine the role of school-based management in healthy school efforts. This research uses qualitative research, where the techniques used are interviews, observation, and documentation.